CONDITIONS, PROBLEMS, AND SOLUTIONS OF ASSOCIATES AND INTERNATIONAL REFUGEES IN INDONESIA IN THE PERSPECTIVE OF NATIONAL LAW AND INTERNATIONAL LAW - Bima Yosua A Tarigan; M. Alvi Syahrin (Journal of Law and Border Protection, 2021)
This paper discusses that Indonesia which is not a contracting state to the 1951 Refugee Convention and 1967 Protocol, but still respect human rights of asylum seekers and international refugees on the principle of non-refoulement. By being unable to refuse the asylum seekers, it will result in the accumulation of those who have the potential to disturb the security and order of the Indonesian people. This paper aims to identify conditions, problems, and provide solutions for asylum seekers and refugees in Indonesian territory from the perspective of national law and international law. This writing uses a normative research method with a juridical-normative approach, which refers to the prevailing laws and regulations. The solution that can be provided is the establish regulations regarding the handling of asylum seekers and refugees, improving communication with the main destination countries, conduct training for officer in dealing with asylum seekers and refugees, and optimally applying the Global Compact on Refugee concept. The results of this paper indicate that national law and international law can provide protection for asylum seekers and refugees.